PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PRODUKTIF SMK - nurjanah, iis (PT. Solusi Komunikasi Terapan, 2023)
This research is based on the importance of improving the professionalism of teachers, especially private vocational teachers in KORWIL III District Bandung in developing competence through the existing activities in Korwil. This research uses qualitative method with